2015
DOI: 10.4028/www.scientific.net/amr.1088.680
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Content and its Influence on the Roughness and Noise Emission during Wood Machining

Abstract: Numerous factors influencing the surface quality of wood after machining, among them we highlight the machining parameters and the properties of the wood. In the analysis of the influence of these factors on machining and in determining the quality measurement systems are used to obtain surface characteristics, these systems are divided into methods of contact and non-contact. The method for mechanical contact performed with the aid of the surface roughness tester is the most valued in the measurement of rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Previous studies by Davis [12] as cited in Mitchual et al [15] suggested that best wood machining results could be obtained at 6% moisture content and the poorest at 20% or more moisture content. Pinheiro et al [19] also observed that the surface roughness of wood increases with increasing moisture content. Therefore, the moisture content of the samples for this study could be considered adequate.…”
Section: Gmelina Arboreamentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies by Davis [12] as cited in Mitchual et al [15] suggested that best wood machining results could be obtained at 6% moisture content and the poorest at 20% or more moisture content. Pinheiro et al [19] also observed that the surface roughness of wood increases with increasing moisture content. Therefore, the moisture content of the samples for this study could be considered adequate.…”
Section: Gmelina Arboreamentioning
confidence: 90%
“…The mean moisture content of the samples just before the test was 14% and 15% for WEFZ and DSDFZ respectively. Reports indicate that samples at lower moisture content have better machining qualities than at higher moisture content [19,8,12], indicating that samples from WEFZ should have performed better than those from DSDFZ but showed otherwise. This could mean that surface quality depends on moisture content to some extent and in this case shaping at 14% or below could generate more machining defects.…”
Section: Shaping Characteristics Of Gmelina Arboreamentioning
confidence: 99%
“…The effect of MC on surface quality in machining differs by wood species and sections [39][40][41]. Pinheiro et al [42] studied the influence of MC on SR and noise emission during wood planning. They observed that an increase in MC led to an increase in roughness and a decrease in noise emission.…”
Section: Srmentioning
confidence: 99%